2020
DOI: 10.12659/msm.919601
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-668-3p Protects Against Oxygen-Glucose Deprivation in a Rat H9c2 Cardiomyocyte Model of Ischemia-Reperfusion Injury by Targeting the Stromal Cell-Derived Factor-1 (SDF-1)/CXCR4 Signaling Pathway

Abstract: Departmental sources Background: Ischemia-reperfusion injury (IRI) results from the restoration of blood supply to ischemic organs, including the heart. Expression of microRNA-668-3p (miR-668-3p) is known to protect the kidney from IRI. This study aimed to investigate the role of miR-668-3p in oxygen-glucose deprivation (OGD) in a rat H9c2 cardiomyocyte model of IRI. Material/Methods: Rat H9c2 cardiomyocytes were cultured in glucose-free Dulbecco's modified Eagle's medium (DMEM) under anaerobic conditions, fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The selection of these genes was based on their fold change rates as well as their implication in I/R-related processes, as published elsewhere. 20 , 21 , 22 Namely, we investigated the expression of Apoptosis Inducing Factor mitochondria associated 1 ( Aifm1 ), Apoptosis Protease-Activating Factor-1 ( Apaf1 ), B-Cell Lymphoma 2 ( Bcl-2 ), Cytochrome c ( Cycs ), Heme Oxygenase 1 ( Hmox-1 ), and Mitogen-Activated Protein Kinase 8 ( Mapk-8 ). Figures 6 A and 6B show that the expression of Apaf-1 and Hmox-1 increased significantly in I/R, as compared with controls.…”
Section: Resultsmentioning
confidence: 99%
“…The selection of these genes was based on their fold change rates as well as their implication in I/R-related processes, as published elsewhere. 20 , 21 , 22 Namely, we investigated the expression of Apoptosis Inducing Factor mitochondria associated 1 ( Aifm1 ), Apoptosis Protease-Activating Factor-1 ( Apaf1 ), B-Cell Lymphoma 2 ( Bcl-2 ), Cytochrome c ( Cycs ), Heme Oxygenase 1 ( Hmox-1 ), and Mitogen-Activated Protein Kinase 8 ( Mapk-8 ). Figures 6 A and 6B show that the expression of Apaf-1 and Hmox-1 increased significantly in I/R, as compared with controls.…”
Section: Resultsmentioning
confidence: 99%
“…However, whether such binding exerts a functional role needs to be tested. CXCR4 is a crucial mediator of hepatic, cardiac, and lung ischemia-reperfusion injury [ 40 , 41 , 42 ]. In the present study, we observed that the reduction of miR-9-5p correlated with enhanced expression of CXCR4 mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the intrinsic mechanisms implicated in RIRI-associated cell death include the disruption of mitochondrial dynamics, resulting in mitochondrial fragmentation. Wei et al revealed that microRNA-668 (miR-668), previously found up-regulated in the RIRI model, has a protective effect during RIRI by inhibiting pathogenic mitochondrial fragmentation and the subsequent apoptosis of renal tubular cells [ 28 ]. Moreover, the induction of miR-668 in RIRI is HIF-1 dependent, while among the miR-688 target genes, only mitochondrial protein 18kDa (MTP18) is associated with mitochondrial dynamics.…”
Section: Different Pathophysiological Mechanisms Of Hif-1α In Renal D...mentioning
confidence: 99%